Progress in Landslide Research and Technology, Volume 2 Issue 1, 2023 - Alcántara-Ayala, Irasema; Arbanas, Željko; Cuomo, Sabatino; Huntley, David; Konagai, Kazuo; Mihalić Arbanas, Snježana; Mikoš, Matjaž; Sassa, Kyoji; Sassa, Shinji; Tang, Huiming; Tiwari, Binod (Progress in Landslide Research and Technology, 2023)
This open access book provides an overview of the progress in landslide research and technology and is part of a book series of the International Consortium on Landslides (ICL). The book provides a common platform for the publication of recent progress in landslide research and technology for practical applications and the benefit for the society contributing to the Kyoto Landslide Commitment 2020, which is expected to continue up to 2030 and even beyond to globally promote the understanding and reduction of landslide disaster risk, as well as to address the 2030 Agenda Sustainable Development Goals.